PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM PERFORMANCE DENGAN DIMODERASI OLEH OWNERSHIP CONCENTRATION - Yenny Vanisa; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to determine the effect of corporate social responsibility on firm performance with ownership concentration as a moderating variable. Firm performance is proxied by return on asset (ROA). Sample is derived by purposive sampling method from non-financial firms listed in SRI KEHATI index from 2017-2019 period. Method used to regress the panel data is General Least Square (GLS) through Eviews 12. This research finds that first, CSR positively and significantly affects firm performance. Second, ownership concentration fails to moderate the effect of CSR towards firm performance. Ownership concentration acts as homologiser moderator, a variable initially known to be able to moderate the relationship between CSR and firm performance, but after being regressed, fails to do so.